Rainfall Interception by Leaf Litter in Central Himalayan Forests - Pathak, P. C.; Rawat, Y. S.; Singh, R. P. (Indian Forester, 1989)
Litter biomass interception by different forest ecosystems in Central Himalaya was assessed during the 1982 monsoon season. Average litter biomass varied from 6.2 to 7.1 t ha-1 and the litter interception renged in between 7.9 to 11.8% of gross rainfall among the sites. The broadleaf species intercepted greater amount of rain water compared to the conifers.